Development Of Innovative Diorama Learning Media To Improve Student Learning Outcomes In Class IV Science And Science Subject - Dwi Asih Fitriyani (Jurnal Pendidikan dan Pengajaran, 2024)
Teachers are still limited in using concrete object learning media in Natural and Social Sciences subjects, so student learning outcomes are low. This study aims to develop innovative diorama learning media to improve student learning outcomes in the material on Indonesian cultural diversity. This type of research is research and development (R&D) with the Borgh and Gall model. The study subjects were learning media experts, learning material experts, and teachers. The population in this study was 25 students. Data collection methods were interview methods, documentation, questionnaires and tests. Data collection instruments were in the form of questionnaires and test questions. Data analysis techniques were quantitative analysis and inferential statistics. Material experts validated the study results with a very feasible category, and media experts with a very feasible category. The results of the t-test, namely using the paired sample t-test on a large and small scale, showed a significant difference after using diorama media. Based on the results of the N-gain test on a small scale, namely 88 (high) and on a large scale, namely 70 (moderate), there was an increase in value between the pretest and posttest. It is concluded that innovative diorama learning media can improve student learning outcomes in Natural and Social Sciences subjects.